2014
DOI: 10.1111/aos.12367
|View full text |Cite
|
Sign up to set email alerts
|

Laser iridotomy and the corneal endothelium: a systemic review

Abstract: ABSTRACT. This study aims to systemically review the effect of laser iridotomy on the corneal endothelium. Searches were performed for studies that either compared corneal endothelial cell density/count, corneal thickness and morphology pre-and postiridotomy, or evaluated the postiridotomy development of corneal decompensation. There were 26 eligible studies. Our review shows that the effect of laser iridotomy on the corneal endothelium has been investigated with varying results. Although it has been demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 63 publications
(175 reference statements)
0
29
1
1
Order By: Relevance
“…Glaucoma drainage device implantation is currently comparable to trabeculectomy in terms of success rate and the possibility of complications [30]. However, glaucoma drainage device implantation is associated with persistent damage to the corneal endothelium [1011121631], contrary to other intraocular procedures including trabeculectomy, in which corneal damage is thought to occur only during the treatment [6789131432]. Lee et al [11] reported that the endothelial cell density of the central cornea was reduced by 12.6% at 12 months and by 15.4% at 24 months after AGV implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Glaucoma drainage device implantation is currently comparable to trabeculectomy in terms of success rate and the possibility of complications [30]. However, glaucoma drainage device implantation is associated with persistent damage to the corneal endothelium [1011121631], contrary to other intraocular procedures including trabeculectomy, in which corneal damage is thought to occur only during the treatment [6789131432]. Lee et al [11] reported that the endothelial cell density of the central cornea was reduced by 12.6% at 12 months and by 15.4% at 24 months after AGV implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering recent evidence from both clinical and experimental studies demonstrating the increased development of nuclear cataract as a consequence of disturbed ocular oxygen gradients caused by vitrectomy (Barbazetto et al, 2004;Holekamp et al, 2005), any iris vascular abnormality would probably affect the oxygen gradients in anterior chamber with pathological consequences. Moreover, there is added potential risk of corneal decompensation after traumatic procedures such as laser iridotomy (Szumny and Szelag, 2014;Wang et al, 2014;Youm et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To perform this function, the corneal endothelium must consist of healthy cells above a given minimum cell density. Corneal endothelial cell loss is induced by various ocular interventions, including cataract surgery,1 trabeculectomy,2 laser iridotomy,3 cyclophotocoagulation,4 pars plana vitrectomy5 and glaucoma implant surgery 6–8. Endothelial cell loss after glaucoma implant surgery is a particularly significant factor, especially with respect to its continuity 6–8…”
mentioning
confidence: 99%